Population diversity of striped snakehead, Channa striata (Bloch, 1793) from Bekasi, West Java and Barito Kuala, South Kalimantan using Cytochrome B gene - Gita Kusuma Rahayu; Dedy Duryadi Solihin; Nurlisa A Butet (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Channa striata or striped snakehead is one of species from family Channidae that widely distributed from India, Southern China to Southeast Asia including Indonesia. It is a commercially important freshwater fish because of its taste and health benefits. High demand of this species trigger many efforts to increase its production, one of them is genetic monitoring. This study used complete Cytochrome b gene sequence of mtDNA for determining genetic variation in wild population of C. striata. C. striata samples (n=31) from two different locations in Indonesia were amplified and analyzed using MEGA ver 7.0. Sequences of 1140 bp complete cyt b gene revealed the presence of 2 haplotypes with 1137 bp conserved sites and 3 bp variable sites (0,26%). Overlapping haplotype was observed in samples from Bekasi, however there were only one haplotype in samples from South Borneo. Interspecies genetic were analysed with species from Genebank and showed that C. striata from Indonesia has close genetic relationships with C. striata from Borneo-Indonesia (MN057164.1) with genetic distance 0%. This study also revealed that C. striata from Indonesia were phylogenetically distinct with C. striata from China with 9,2%K2P genetic distance. Complete cyt b gene has been proven for assessing phylogenetic relationships and population diversity of C. striata in Indonesia. Abstrak Channa striata atau ikan gabus haruan adalah salah spesies dari famili Channidae yang tersebar luas mulai dari India, Cina bagian selatan hingga Asia Tenggara termasuk Indonesia. Hewan ini dikenal sebagai jenis ikan air tawar yang bernilai ekonomis karena rasa dan manfaat kesehatannya. Permintaan yang tinggi akan spesies ini mendorong upaya peningkatkan produksinya salah satunya dari segi pengawasan genetiknya. Penelitian ini menggunakan sekuen utuh gen Cytochrome b (cyt b) pada DNA mitokondria untuk menentukan variasi genetik populasi liar C. striata. Sampel C. striata (n=31) Indonesia asal dua lokasi berbeda berhasil diamplifikasi dan dianalisis menggunakan MEGA ver 7.0. Sekuen utuh gen cyt b sepanjang 1140 bp yang didapat menunjukkan adanya 2 haplotipe dengan 1137 bp situs konservatif dan 3 bp situs bervariasi (0,26%). Haplotipe yang tumpang tindih ditemukan pada sampel asal Bekasi, dan hanya ada satu haplotipe pada sampel asal Kalimantan Selatan. Analisis genetik interspesies dengan spesies dari Genebank menunjukkan sampel C. striata memiliki kedekatan genetik dengan C. striata (MN057164.1) asal Kalimantan-Indonesia dengan jarak genetik 0%. Penelitian ini juga menunjukkan bahwa C. striata dengan C. striata asal Cina dengan rata-rata jarak genetik 9,2%. Gen cyt b utuh mampu menjelaskan kekerabatan filogenetik dan memberikan informasi keragaman populasi C. striata asal Indonesia.